2022
DOI: 10.3390/ijms23158078
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Trace Metals and Their Potential Transplacental Transfer in Pregnancy

Abstract: With the ever-growing concern for human health and wellbeing, the prenatal period of development requires special attention since fetuses can be exposed to various metals through the mother. Therefore, this study explored the status of selected toxic (Pb, Cd, Ni, As, Pt, Ce, Rb, Sr, U) and essential trace metals (Mn, Co, Cu, Zn, Se) in the umbilical cord (UC) sera, maternal sera, and placental tissue samples of 92 healthy women with normal pregnancies. A further aim focuses on the potential transplacental tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Compared with other studies, the concentrations of Cd in maternal blood, placenta, and umbilical cord blood in Kunming, China were higher than those in Slovenia, 18 Germany (Saudi), 19 Sweden, 20 and Beijing and Zhejiang, China, 21,22 but the concentrations of Cd in maternal blood and umbilical cord blood in Kunming, China were lower than those in Catalonia, Spain 23 and Brazil (Rio de Janeiro). 24 Studies in other regions of the world have reported that the content of Cd in the placenta is higher than that in maternal blood and umbilical cord blood, [25][26][27] which is consistent with our results. As a temporary multifunctional organ connecting the mother and fetus, 28 the placenta plays an important role in filtering and blocking harmful substances.…”
Section: Comparison Of Mt and Cd-mt Expression Levelssupporting
confidence: 91%
“…Compared with other studies, the concentrations of Cd in maternal blood, placenta, and umbilical cord blood in Kunming, China were higher than those in Slovenia, 18 Germany (Saudi), 19 Sweden, 20 and Beijing and Zhejiang, China, 21,22 but the concentrations of Cd in maternal blood and umbilical cord blood in Kunming, China were lower than those in Catalonia, Spain 23 and Brazil (Rio de Janeiro). 24 Studies in other regions of the world have reported that the content of Cd in the placenta is higher than that in maternal blood and umbilical cord blood, [25][26][27] which is consistent with our results. As a temporary multifunctional organ connecting the mother and fetus, 28 the placenta plays an important role in filtering and blocking harmful substances.…”
Section: Comparison Of Mt and Cd-mt Expression Levelssupporting
confidence: 91%
“…Additionally, these mechanisms may differ considerably from other environmental exposures, given that in contrast to many other toxicants, relatively little cadmium crosses the placenta to directly impact the fetus in animals and human studies; instead, the placenta highly concentrates cadmium [ 13 , 14 , 15 , 16 ]. This results in cadmium levels in placental tissue being four times higher than cadmium levels in maternal serum and six times higher than cadmium level in umbilical cord serum [ 17 ].…”
Section: Introductionmentioning
confidence: 99%